Linear Motor System Identification and Simulation Experiments Based on LabVIEW - Wu, Xiaoyan; Wang, Shu (Manufacturing Technology Journal, 2024)
There are currently many control methods for linear motors, and the focus of controlling the motor should be different for different application needs. In general applications, simple PID control can meet the application requirements, but in precision motion situations with high requirements for motion accuracy, response speed, and stability, PID control is often difficult to achieve satisfactory control results, which requires the application of more advanced control strategies to complete. At present, combining multiple control algorithms and concentrating the advantages of each algorithm while trying to overcome each other's disadvantages has become a major trend in the development of motor control theory. High speed, high efficiency, high precision become the development direction of the current numerical control equipment, linear motor because of its unique performance, now widely used in a variety of precision positioning occasions. Aiming at the requirements of high speed response and high precision of linear motor, the linear motor system is designed based on LabVIEW software and NI acquisition card, including hardware composition and software algorithm. In the LabVIEW simulation environment and the actual control system, the conventional PID algorithm and fuzzy PID algorithm are used to control, and the control results are compared. The experimental results show that compared with the PID control, the fuzzy PID algorithm has obvious advantages in improving the control accuracy, anti-interference ability, reducing the overshoot and improving the system response speed.
Keywords: Llinear motor; System identification; LabVIEW; Fuzzy PID; Simulation experiment